PENINGKATAN HASIL BELAJAR SISWA PADA MATERI STRUKTUR BUMI MELALUI PENERAPAN TEORI PEMBELAJARAN KONSTRUKTIVISME DI KELAS V SDN 9 LIMBOTO - Sawal Sawal; Herson Anwar; Dewi Darmiyani Napu (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2026)
AbstractThis study aims to improve the learning outcomes of science in fifth grade students of SDN 9 Limboto through the application of constructivism learning. The type of research used is classroom action research which is carried out in 2 cycles. The subjects of this study were 16 students of class V B. While the object of this research is the application of Constructivism learning theory to improve the results of science lessons on the material of Earth Structure at SDN 9 Limboto. Data collection techniques are observation, interviews, tests and documentation. Based on the results of the study it can be concluded that the application of constructivism learning can improve the learning outcomes of science in fifth grade students of SDN 9 Limboto. This increase can be seen from the percentage of learning completeness which has increased gradually. In cycle I, the average value of students reached 71 with a classical completeness percentage of 56%. After the action in cycle II, the average value became 78 with a classical completeness of 75%. In addition, student learning outcomes after the application of constructivism learning showed a better increase compared to before the application of the method. The application of constructivist learning is also able to increase students' interest and willingness to participate in learning activities in the classroom, so that the learning process takes place more actively, effectively, and meaningfully.Keywords: Constructivist Learning, Learning Outcomes, Earth Structure Material AbstrakPenelitian ini bertujuan untuk meningkatkan hasil belajar IPAS pada siswa kelas V SDN 9 Limboto melalui penerapan pembelajaran konstruktivisme. Jenis penelitian yang digunakan yaitu penelitian Tindakan kelas yang dilaksanakan dalam 2 siklus. Subjek penelitian ini adalah siswa kelas V B yang berjumlah 16 siswa. Sedangkan Objek penelitian ini yaitu penerapan teori pembelajaran Kontruktivisme untuk meningkatkan hasil pelajaran IPAS pada materi Struktur Bumi di SDN 9 Limboto. Teknik pengumpulan data yaitu observasi, wawancara, tes dan dokumentasi. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan pembelajaran konstruktivisme dapat meningkatkan hasil belajar IPAS pada siswa kelas V SDN 9 Limboto. Peningkatan tersebut terlihat dari persentase ketuntasan belajar yang mengalami kenaikan secara bertahap, Pada siklus I, nilai rata-rata siswa mencapai 71 dengan persentase ketuntasan klasikal sebesar 56%. Setelah tindakan pada siklus II, nilai rata-rata menjadi 78 dengan ketuntasan klasikal sebesar 75%. Selain itu, hasil belajar siswa setelah penerapan pembelajaran konstruktivisme menunjukkan peningkatan yang lebih baik dibandingkan sebelum penerapan metode tersebut. Penerapan pembelajaran konstruktivisme juga mampu meningkatkan minat dan kemauan siswa dalam mengikuti kegiatan pembelajaran di dalam kelas, sehingga proses pembelajaran berlangsung lebih aktif, efektif, dan bermakna. Kata Kunci: Pembelajaran Konstruktivisme, Hasil Belajar, Materi Struktur Bumi